Morphometric differences of Spirlin, Alburnoides Bipunctatus Bloch 1782 from the Major Catchements of Transylvania - Tudor PĂPUC (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies, 2017)
Spirlin (Alburnoides bipunctatus) is found in great numbers in most Transylvanian rivers. The species has an important role in the ecosystems in which it is found in terms of feeding and habitat occupation. The morphmetric characthers of this species vary between different habitats, outlining morphometric plasticity. Morphometric profiles were made for different populations of Spirlin, to evaluate differences in body shape. Considering that different environmental conditions influence the morphology of Spirlin populations, morphometric characteristics were determined. In order to assess differences in spirlin body shape, specimens from the four major Transylvanian catchments were collected by angling techniques. The specimens were preserved and transported to the University of Agricultural Sciences and Veterinary Medicine, Cluj-Napoca, where morphometric measurements and weight determinations were conducted in the Physiology of Aquatic Organisms Laboratory. Spirlin from Mures, Somes, Cris and Viseu catchments were studied, as it follows: 21 specimens from Aries River (Mures catchment), 61 specimens from the river Crisul Repede (Cris catchment), 21 specimens from Somesul Mic River (Somes catchment) and 20 specimens from Viseu River. A number of 39 determinations were made. The obtained results reflect the morphometric differences among populations of Spirlin from some Transylvanian main rivers.